2021
DOI: 10.3390/atmos12030377
|View full text |Cite
|
Sign up to set email alerts
|

Particle Emissions and Disc Temperature Profiles from a Commercial Brake System Tested on a Dynamometer under Real-World Cycles

Abstract: The particle emissions from a commercial brake system utilizing copper-free pads have been characterized on a brake dynamometer under two real-world driving cycles. These included a novel cycle developed from analysis of the database of the World Harmonized Test Procedure (WLTP-Brake) and a short version of the Los Angeles City Traffic cycle (3h-LACT) developed in the framework of the European LowBraSys project. Disc temperature measurements using an array of embedded thermocouples revealed a large temporal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Figure 10 shows the mean particle number concentration curve for the two brake events with the highest initial velocity (#101 and #106) from Trip 10. These are very well suited to identify ultrafine particles in the WLTP Brake Cycle [33]. The figure shows that pair 1 and pair 2 emit a reproducible size distribution.…”
Section: Brake Shoe Compositionsmentioning
confidence: 96%
“…Figure 10 shows the mean particle number concentration curve for the two brake events with the highest initial velocity (#101 and #106) from Trip 10. These are very well suited to identify ultrafine particles in the WLTP Brake Cycle [33]. The figure shows that pair 1 and pair 2 emit a reproducible size distribution.…”
Section: Brake Shoe Compositionsmentioning
confidence: 96%
“…We estimated the difference due to cooling air flow to be about 8.1% for PM10 based on the slope of the linear regression line, with a similarity R 2 of 0.981 (r = 0.65, p<0.1, n=5) when comparing the two cooling flow rates of 1 m 3 /min and 10 m 3 /min. In a previous study, there was also no significant difference in the PM2.5 to PM10 ratio when the cooling flow rate was increased from 15 m 3 /min to 20 m 3 /min [44]. Therefore, the current results were consistent with those of previous studies, and the PM10 and PM2.5 emissions were reproduced under very low air flow conditions (1 m 3 /min) using the JASO C470 method and under high air flow conditions (10 m 3 /min) equivalent to those of the GTR24 method.…”
Section: Cooling Air Flow Effect For Particle Mass Emissionmentioning
confidence: 75%
“…The difference between the PM10 (2.03) and PM2.5 (1.99) emission factors of the two experiments indicates the uncertainty of the experiments. The decrease in losses in the tunnel by decreasing the Stokes number (increasing collection efficiency, as shown in the PM to brake wear factors) at increasing cooling air flow rate should have a strong impact, indicating the uncertainty of the experiment [44]. The extremely low cooling air flow rate (1 m 3 /min) in the JASO C470 method used in this study is a limitation of the structural requirements for future tests using automobiles, and it has been used in previous studies to collect sample air at 0.1-0.3 m 3 /min [45], 0.5-1.3 m 3 / min [46], and 1.48 m 3 /min [47].…”
Section: Cooling Air Flow Effect For Particle Mass Emissionmentioning
confidence: 99%
“…According to other studies, iron was the most prevalent metal found in all experiments addressing brake wear debris [255–257]. Mamakos et al have used an airborne PM measuring stand with medium EU passenger car hardware and wear particles generated by NAO and LM pairs of pads rubbered into grey cast iron discs for a dynamometric inertia bench [258]. In an over-pressured case, the brake assembly was enclosed with a regulated supply of clean air and a high sampling efficiency isokinetic sampling.…”
Section: Wear Studiesmentioning
confidence: 99%